Studying the effect of the number of laser pulses on the structure, morphology, and optical properties for a thin film of GO-Ag nanocomposites. Issue 1 (September 2021) - Al-Mousawi, Mousa Muhammad Ali; Al-Nafiey, Amer; Al-Dahesh, Ghaleb
Abstract: In this paper, studying the effect of the different numbers of laser pulses on graphene oxide -silver nanoparticles (GO-Ag NPs) thin film prepared by the pulse laser deposition (PLD) on silicon and quartz substrates. The laser using in PLD is an ND-YAG laser with a wavelength (1064 nm)m with a repetition rate of 6 Hz with a laser pulse duration (9 ns). Atomic force microscopy AFM and XRD using for analysis of the thin film, the results showed the possibility of preparing thin films with different sizes of granule and crystalline sizes on the nanoscale. Also, show that the granular size and crystal size of the nanoparticles decrease with the increase in the number of laser pulses with the constant energy. Moreover, the optical properties measurements showed that the absorbance and absorption coefficient increase with the increase in the number of pulses when the energy is constant, while the energy gap decreases with increasing the number of pulses These results were promises to producing the thin film for Graphene oxide-silver nanocomposites for different applications compatible with it.